Application of subject-specific helmets for the study of human visuomotor behavior using transcranial focused ultrasound: a pilot study. (November 2022) - Park, Tae Young; Jeong, Ji Hyeok; Chung, Yong An; Yeo, Sang Hoon; Kim, Hyungmin
Highlights: We proposed the framework of transcranial focused ultrasound (tFUS) stimulation integrating our two previously proposed methods for tFUS transducer configuration optimization and a subject-specific 3D-printed helmet. To validate this framework, tFUS stimulations were applied to the left dorsolateral prefrontal cortex (DLPFC) while human participants were performing anti-saccade tasks. The result indicates that the cortical stimulation using our tFUS setup effectively reduces the error rates of anti-saccade tasks, whereas no significant effect was observed on their latencies. We demonstrated that our tFUS framework can be effectively used in human behavioral study, and our tFUS stimulation targeted to the DLPFC could generate a neuromodulatory effect on AS behavior. Abstract: Background and objective: As a novel non-invasive human brain stimulation method, transcranial focused ultrasound (tFUS) is receiving growing attention due to its superior spatial specificity and depth penetrability. Since the focal point of tFUS needs to be fixated precisely to the target brain region during stimulation, a critical issue is to identify and maintain the accurate position and orientation of the tFUS transducer relative to the subject's head. This study aims to propose the entire framework of tFUS stimulation integrating the methods previously proposed by the authors for tFUS transducer configuration optimization and a subject-specific 3D-printed helmet, and to validate this complete setup in a human behavioral neuromodulation study. Methods: To find the optimal configuration of the tFUS transducer, a numerical method based on subject-specific tFUS beamlines simulation was used. Then, the subject-specific 3D-printed helmet has been applied to effectively secure the transducer at the estimated optimal configuration. To validate this tFUS framework, a common behavioral neuromodulation paradigm was chosen; the effect of the dorsolateral prefrontal cortex (DLPFC) stimulation on anti-saccade (AS) behavior. While human participants (n=2) were performing AS tasks, tFUS stimulations were randomly applied to the left DLPFC right after the fixation target disappeared. Results: The neuromodulation result strongly suggests that the cortical stimulation using the proposed tFUS setup is effective in significantly reducing the error rates of anti-saccades (about -10 %p for S1 and -16 %p for S2), whereas no significant effect was observed on their latencies. These observed behavioral effects are consistent with the previous results based on conventional brain stimulation or lesion studies. Conclusions: The proposed subject-specific tFUS framework has been effectively used in human neuromodulation study. The result suggests that the tFUS stimulation targeted to the DLPFC can generate a neuromodulatory effect on AS behavior.